2013
DOI: 10.1063/1.4819015
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation-controlled gold-induced-crystallization for selective formation of Ge(100) and (111) on insulator at low-temperature (∼250 °C)

Abstract: Selective formation of Ge(100) and (111) on amorphous-insulator at low-temperatures (∼250 °C) is realized through gold-induced-crystallization using a-Ge/Au/SiO2 stacked-structures by combining interface-energy-modulation of substrates. Introduction of thin-Al2O3 layers (∼7 nm thickness) at a-Ge/Au interfaces enables large-grain (≥20 μm) Ge(111) formation, which is speculated to be due to suppression of random bulk-nucleation and domination of (111)-oriented interface-nucleation on SiO2. To examine this specul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 26 publications
2
82
0
Order By: Relevance
“…Research groups at Kyushu University and Tsukuba University have individually studied the eutectic-metal induced crystallization of Si [55], Ge [56,57], and Si 1−x Ge x [58,59], aiming for orientation control. From a technological point of views, Park et al [60] and Toko et al [61] individually demonstrated the sub-200°C formation of highly (111)-oriented poly-Ge films on flexible plastic substrates.…”
Section: Solid-phase Crystallization (Spc) Technology Of Ge 1−x Sn Xmentioning
confidence: 99%
“…Research groups at Kyushu University and Tsukuba University have individually studied the eutectic-metal induced crystallization of Si [55], Ge [56,57], and Si 1−x Ge x [58,59], aiming for orientation control. From a technological point of views, Park et al [60] and Toko et al [61] individually demonstrated the sub-200°C formation of highly (111)-oriented poly-Ge films on flexible plastic substrates.…”
Section: Solid-phase Crystallization (Spc) Technology Of Ge 1−x Sn Xmentioning
confidence: 99%
“…Located at 27.51, the peak had a FWHM value of only 0.161. This single (111) orientation was explained from the view point of the interfacial energy minimization between the Ge layer and the SiO 2 substrate [22][23][24]. The crystal seed originating from pre-annealing had a different orientation compared to crystal grains induced by the MIC process, causing a conflict that slowed mutual diffusion between Al and Ge.…”
Section: Resultsmentioning
confidence: 98%
“…All thin films have a sharp peak around 13.7˚ indicating preferential (111)-orientation planes. The (111)-orientation planes are interpreted from the viewpoint of the minimal interfacial energy between Ge thin film and SiO 2 substrate [21]. The FWHM values of the sharp peak of XRD rocking curve are plotted in the insert figure, which indicates that the lower annealing temperature provides weaker (111)-orientation planes but larger FWHM values.…”
Section: S G Dong Et Al Journal Of Materials Science and Chemical mentioning
confidence: 99%